2020
DOI: 10.1016/j.ihj.2020.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Acute Coronary Syndrome admissions and outcome during COVID-19 Pandemic–Report from large tertiary centre in India

Abstract: Few studies from various countries have reported decline in Acute Coronary Syndrome (ACS) admissions to hospital during COVID-19 pandemic. We studied the impact of COVID-19 strict lockdown on ACS admission in a tertiary referral hospital in India. This showed 43% decline in admissions (n=104 vs mean n=183) and even in those who got admitted, there was a delay in presentation compared to previous year, which was reflected in the outcome of patients. Government and health organizations should educate the public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Several centres have reported a decrease in admissions during the pandemic, 1,2,6 whereas others have found no significant difference compared with pre-COVID-19 levels. 5 With regard to the type of MI, most studies have shown a decrease in NSTEMI admissions during the COVID-19 pandemic, but mixed results pertaining to STEMI presentations.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Several centres have reported a decrease in admissions during the pandemic, 1,2,6 whereas others have found no significant difference compared with pre-COVID-19 levels. 5 With regard to the type of MI, most studies have shown a decrease in NSTEMI admissions during the COVID-19 pandemic, but mixed results pertaining to STEMI presentations.…”
Section: Discussionmentioning
confidence: 95%
“…This is in keeping with reports from other studies, and is testament to the robustness of these medical systems in maintaining a high level of cardiovascular care despite the pandemic. 1,6,14 Data on PCI volumes provide some insights into how COVID-19 has affected elective procedures. The decrease in PCI in the present study was driven largely by data from Singapore, where there was an active push to reschedule non-urgent elective cardiac catheterisation.…”
Section: Discussionmentioning
confidence: 99%
“…Admissions for acute coronary syndrome (ACS) had decreased significantly by more than one third over three months in India since the lockdown. 31 , 32 There was greater reductions in the number of NSTEMI than STEMI. The decrease in the hospitalisations corroborated with the lockdown and the difference in the rates lessened in the second phase of lockdown.…”
Section: Covid-19 Pandemic and Cardiovascular Carementioning
confidence: 97%
“…In a hospital located in Hong Kong, delays in performing percutaneous coronary interventions for patients who visited an emergency department for acute myocardial infarction (AMI) were reported (Lotfi et al, 2020). A study from India also observes reduced cases of AMI patients and deterioration in patient outcomes (Showkathali et al, 2020). Care for nonacute conditions also decreased during the pandemic.…”
Section: Indirect Effects Of the Covid-19 Pandemicmentioning
confidence: 99%